SFAS No. 106 and Benefit Reductions in Employer-Sponsored Retiree Health Care Plans. - Mittelstaedt, H. Fred; Nichols, William D. (The Accounting Review, 1995)
Abstract Examines possible determinants of firms' decisions to reduce benefits of retiree health care plans. Increasing contracting cost caused by the financial reporting consequences of Statement on Financial Accounting Standards SFAS No. 106; Financial weakness independent of SFAS No. 106; Firm-specific changes in retiree health care costs.